PENGARUH RASIO KEUANGAN, INFLASI DAN SUKU BUNGA TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR DI BEI - Abdul Jait Tjereni; Dhian Andanarini Minar Savitri (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2015)
The development of the capital market in Indonesia is very rapidly.This is an indicator that the capital market is an alternative source offunding in addition to banking, in addition to the growing capital marketsalso showed that the confidence of investors will invest in Indonesia capitalmarket is quite good. The information required by the investors in the capitalmarkets is not only a fundamental information, but also information that istechnical in nature. The fundamental nature of the information obtainedfrom the financial reports of companies, and the technical nature of theinformation obtained from outside companies such as inflation, interest ratesand other factors.The samples of this research are company manufacturing food andbeverage sector in 2008-2012 by using 16 companies with purposivesampling method. The results of the research with multiple linear regressionshowed that the CR, DER, TAT, ROA, PER and interest rate do not haveeffect on stock return. While inflation has a negative significant effect onstock returns.